2011
DOI: 10.1016/j.ijrobp.2009.12.061
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Placebo-Controlled Trial of Bevacizumab Therapy for Radiation Necrosis of the Central Nervous System

Abstract: Purpose-To conduct a controlled trial of bevacizumab for the treatment of symptomatic radiation necrosis of the brain.Methods and Materials-Fourteen patients were entered into a placebo-controlled randomized double-blind study of bevacizumab for the treatment of central nervous system (CNS) radiation necrosis. All patients were required to have radiographic or biopsy proof of CNS radiation necrosis and progressive neurological symptoms or signs. Eligible patients received irradiation for head and neck carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
425
2
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 628 publications
(459 citation statements)
references
References 18 publications
(17 reference statements)
12
425
2
9
Order By: Relevance
“…35 Targeting VEGF has a strong biological rationale, and promising clinical data are emerging for the use of bevacizumab, a monoclonal antibody against VEGF in the treatment of radiation-induced cerebral necrosis. 36 Bevacizumab has also been reported to result in neurologic improvement in a patient with radiation myelopathy. 37 Erythropoietin (EPO) has been used extensively over the past 10 to 15 years for the treatment of anemia in cancer patients.…”
Section: Strategies To Mitigate Injurymentioning
confidence: 99%
“…35 Targeting VEGF has a strong biological rationale, and promising clinical data are emerging for the use of bevacizumab, a monoclonal antibody against VEGF in the treatment of radiation-induced cerebral necrosis. 36 Bevacizumab has also been reported to result in neurologic improvement in a patient with radiation myelopathy. 37 Erythropoietin (EPO) has been used extensively over the past 10 to 15 years for the treatment of anemia in cancer patients.…”
Section: Strategies To Mitigate Injurymentioning
confidence: 99%
“…True progressive brain tumors are malignancies with increased vascularity, immature leaky vessels, and upregulated VEGF expression resulting in higher BF, BV and PS. On the other hand, the moderate PS observed in TIN is likely mediated by the release of VEGF in the pathogenesis of radiation necrosis [41]. In addition, susceptibility artefacts from blood products (hemorrhage, thrombus) and calcification can potentially complicate the analysis of DSC-MR studies while PCT is not affected by these artefacts [39,42].…”
Section: Differentiation Of True Progression From Post-treatment Effectsmentioning
confidence: 99%
“…However, bevacizumab is an anti-angiogenic drug recognized for its role in pruning vessels and promoting blood supply, which is inconsistent with the above inference [25]. We believe that several mechanisms are [26].Among many previous studies, only a few have reported several recurrence cases [4][5][6][7][8][9][10]. Our literature review shows that previous researchers may have missed progression in many cases reported as "without progression" due to individual differences in bevacizumab sensitivity, short follow-up times after bevacizumab is discontinued, or death shortly after bevacizumab is discontinued.…”
Section: Discussionmentioning
confidence: 79%
“…Compared to previous reports, most studies [4][5][6][7][8][9][10] only reported the efficacy of bevacizumab in the treatment of radiation-induced cerebral necrosis, while there were fewer studies on the recurrence and progression of radiation-induced cerebral necrosis after treatment. No studies have yet explored the reasons for recurrence and progression.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation